Main directions for increasing the efficiency of financing small and medium businesses engaged in the agricultural sector - Ahmadova, Leyla (Dunakavics, 2024)
The article discusses the specifics of small and medium-sized businesses in the agricultural sector of the economy. Various forms of financing and investment of funds in agriculture are analyzed. Various ways to ensure financial efficiency and sustainability in small and medium-sized businesses are considered. The validity of state support for small and medium-sized businesses in the agricultural sector of the economy is given. The possibilities of attracting private investment and the possibility of operating small and medium-sized businesses in the agricultural sector of the economy are characterized. Forms of state support are analyzed, as well as the possibilities of using preferential loans and financial resources allocated from the country’s budget and transferred to the balance sheet of related financial institutions.